The science and practice of periodization: A brief review - Turner, A. (Strength and Conditioning Journal, 2011)
Periodization represents an optimal strategy for organizing strength and conditioning programs. The selected strategy, however, should be based on the level of the athlete and constraints of the competitive season. A common theme throughout all the periodization protocols is the need to manipulate volume, progress from general to sport-specific training and dissipate fatigue to the latter, the use of precompetitio tapers appears evidently beneficial, although enough anecdotal evidence exists to validate the use of periodization, further investigation is required to understand its use and limitations to elite level athletes across extended periods (e. g. >4 yerars). Until such time, however, its use is recommended and edvocated by the research herin.